(untitled) (Journal of Ideas in Health, 2022)
Background: International efforts to confront the COVID-19 pandemic are joining forces by accelerating the pace of vaccination. This study aims to explore the attitude and the intent to get vaccinated against COVID-19 among healthcare providers (HCPs) in Iraq. Methods: A cross-sectional survey was conducted in January 2021 using web-based facilities to access the respondents. The data were collected through a semi-structured and self-administered questionnaire, including sociodemographic and close-ended questions related to attitude and intention toward COVID-19 vaccination. Bivariate and multivariate logistic regression were recruited to predict variables. The statistical significance is considered at less than 0.05. Results: Data of 209 HCPs with a mean age of 45.12 (± 6.37) years have undergone final analysis. Most of the HCPs were males (112, 53.6%) and nurses (110, 52.6%), who had close contact (64.6%) with COVID-19 patients, and forty percent have been infected with COVID-19. Overall, 115 HCPs (58.0%) reported intention to get vaccinated compared to 94 (42.0%) who declined vaccination. Variables associated with intention to get vaccinated among HCPs were high attitude toward COVID-19 vaccination (odds ratio (OR) = 1.740, 95% confidence interval (CI): 0.799, 3.786), aged less than 45 years (OR = 3.713; 95% CI: 1.647, 8.367), married (OR = 2.155; 95% CI: 0.984, 4.720), highly educated (OR = 2.657; 95% CI: 1.202, 5.871), doctors (OR = 3.153; 95% CI: 1.428, 6.963), contracted with COVID-19 (OR = 4.119; 95% CI: 1.623, 10.455), directly engaged in management of COVID-19 patients (OR = 3.962; 95% CI: 1.569, 10.005), and had lost a close relative due to COVID-19 (OR = 5.698; 95% CI: 1.506, 12.564). Conclusion: The urgent need to improve the COVID-19 vaccine uptake rates among Iraqis requires a positive attitude and a high vaccination rate among HCPs.